The presumption: race and injustice in the United States - Jones, D. Marvin (Bloomsbury Academic, 2024)
"This powerful book on racism in the United States argues that a threatening narrative originating in slavery continues to link Black people to inferiority, dangerousness, and crime, causing them to be presumed guilty by society and U.S. legal systems"--